COMPARISONS OF THE PURCHASING AND PRODUCTION LOT SIZING METHODS - Chotayakul, Supatchaya (Srinakharinwirot University Journal of Sciences and Technology, 2023)
The objective of this research is to determine optimal purchase and production lot size of each product that meets demand at minimum total cost of purchase and production including purchase costs, set up costs, production costs, and holding costs, and to compare results of total production cost and solving time between the methods of a dynamic lot-sizing production and purchase model and dynamic lot sizing model purchase and production combination of the whole production line. Comparing the results between the two methods shows that the total cost and the solving time of the dynamic lot sizing model production and purchase combination of the whole production line is less than the other method.